Management of Infertility due to Bilateral Tubal Blockage, PCOD & Endometrial Polyp by Ayurvedic Regime: A Case Study - Prachi Gupta; Poonam Choudhary (AYUSHDHARA, 2022)
Infertility is one of the predominant health issues, affecting 10-15% of reproductive- aged couples. An infertility evaluation should be considered in any couple that has failed to conceive in one year. Infertility can be subdivided into primary infertility (no prior conception) and secondary infertility (infertility following at least 1 prior conception). Here it is the case of primary infertility. In Ayurveda it can be correlated with Anaptaya Vandhya (that is who never has conceived) and Apraja Vandhya (that lady who never have conceived but can conceive by eliminating the underlying cause). In this case study, Ayurvedic management successfully treat the primary infertility. Main clinical finding: A married Hindu female patient of 28 years of age visited to OPD of National institute of Ayurveda, Jaipur on 24 October 2020 with chief complaint of wants issue since 3 years. She had associated complaint of sometimes milk like discharge from breast since 3 years. Diagnosis: Her HSG scan suggestive of right fallopian tube fimbrial block & left fallopian tube cornual blockage. Her USG scan suggestive of bilateral polycystic ovary & a tiny echogenic polyp of size 3.7x2.3mm in mid part of endometrial cavity. Her prolactin level was found elevated. Interventions: Treatment given was Beejasamskara, Uttarbasti with Apamarga kshara tail & Shudah bala tail along with oral medication. Outcome: She conceived after taking 6 months of treatment. She was given proper antenatal care along with garbhsamskara. She delivered a healthy female baby of weight 3.03kg on 7th Jan 2022. Conclusion: This case study shows the potential of Beejasamskara, Uttarbasti in the management of infertility and the role of Garbhsamskara during the antenatal period.